Teacher Training between the Museum and the Early Childhood Education - Franca Zuccoli (Universidade Federal do Rio Grande do Sul, 2015)
Art education in early childhood education schools and at museums with children aged 3 to 6 is a different way to relate to the potential of children and educators. In this paper we emphasize the importance of the teacher training carried out at museums, where contact with artwork is an element in skills development. The concept of artistic creation is characterized by implications of choices, thoughts, attempts and changes leading to a visible and shared production. These same actions can be carried out, after the experience at the museum, if the museum itself is offered as a stimulus for new hypotheses.